2015
DOI: 10.2174/1574886310666150729112903
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Disproportionality Analysis of Pharmacovigilance Databases in Safety Regulatory Actions: a Systematic Review

Abstract: It was not found any safety signal issued by drug regulatory agencies exclusively generated by DA. More research devoted to this issue is needed, since the value of these methods on drug safety signaling and their impact on drug regulation actions remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Supporting Information Table S1, which is available online, defines calculation of ROR and its 95% confidence interval (CI). 16 An ROR with a 95% CI that not encompass 1.0 suggests "statistical significance," 17 and it has been suggested that an ROR greater than 4.0 indicates a "large" effect size. Secondary analyses were performed by selecting D-penicillamine as a positive control (because this drug is known to be associated with the induction or exacerbation of MG) 18 and acetaminophen as a negative control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting Information Table S1, which is available online, defines calculation of ROR and its 95% confidence interval (CI). 16 An ROR with a 95% CI that not encompass 1.0 suggests "statistical significance," 17 and it has been suggested that an ROR greater than 4.0 indicates a "large" effect size. Secondary analyses were performed by selecting D-penicillamine as a positive control (because this drug is known to be associated with the induction or exacerbation of MG) 18 and acetaminophen as a negative control.…”
Section: Discussionmentioning
confidence: 99%
“…The main disproportionality explored the reporting odds ratio (ROR) of reporting MG (relative to all other ADRs) for statins. Supporting Information Table S1, which is available online, defines calculation of ROR and its 95% confidence interval (CI) . An ROR with a 95% CI that not encompass 1.0 suggests “statistical significance,“ and it has been suggested that an ROR greater than 4.0 indicates a “large” effect size.…”
Section: Methodsmentioning
confidence: 99%
“…We further downgraded the quality of evidence due to reporting bias because very small proportion of primary studies that examined benefits of atypical antipsychotics also examined drug-induced QT prolongation. Retrospective post-marketing case reports collection is biased because the reporting depends on clinician opinion regarding the association between ventricular tachycardia and administration of antipsychotic drugs (109).…”
Section: Discussionmentioning
confidence: 99%
“…(114,115,120). Proactive technologically advanced pharmacovigilance applications should be implemented to decrease the risk of drug-induced QT prolongation and cardiac arrhythmias (109,(121)(122)(123)(124).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review highlighted that only a minority of studies aimed at confirming or supporting previous regulatory decisions on a given safety aspect [52], thus strengthening the aforementioned concept that DAs do not usually support, on their own, regulatory actions but must be integrated with other data sources.…”
Section: Investigate the Likelihood Of Drug-drug Interactionsmentioning
confidence: 99%